Medição de desempenho organizacional nas imobiliárias: um estudo na cidade do Natal-RN - Ribeiro, João Maria Montenegro (2006)
The purpose of this paper is to identify how real estate companies from the city of Natal measure their organizational performance. Traditionally these companies measure their performance using financial measures; however, the technological improvement, the internationalization of the economy and the change in consumer behavior all demand better products and services, and other measuring models. Those changes motivate organizations to continually improve the quality of their products and services. In this way, these companies need to associate their financial results to their global performance. Therefore, it is necessary to have organizational performance models that associate financial and non-financial measures to the strategies of the companies. The research also tries to identify which performance indicators are used by these companies, as well as to test a model who questions: a) if there is any relationship between managers´ characteristics and performance measuring systems´ characteristics; b) if there is any relationship between the company s characteristics and the characteristics of the measuring system used to evaluate its organizational performance and c) finally to verify if there is a relationship between the characteristics of the measuring system and the company s performance. The information which served as a basis for the study was obtained through an empirical research, with questionnaires, answered by 66 (sixty six) companies from the city of Natal, capital of the state of Rio Grande do Norte. The results show that none of the companies investigated use any of the performance measurement models proposed in the modern literature. However, they use on an isolated way some of the measures those models, including some measures from adopted in the Balanced Scorecard, as well as the benchmarking process, making comparisons with the performance of their competitors. The research also reveals that either bigger companies, companies with more experienced managers or with better performance show better performance measurement systems